ANALISIS PENGEMBANGAN STRATEGIS PEMASARAN PUPUK ORGANIK MERK BIOGRANO ORGANIS PADA PT. SUMBER MULYA GRAND ORGANIK BLITAR - ahmad yufron (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2025)
The development of a strategic marketing approach is a crucial factor in supporting company growth and competitiveness in an increasingly competitive business environment. PT. Sumber Mulya Grand Organik Blitar, as a producer of organic fertilizer under the BIOGRANO Organis brand, requires an effective, accurate, and sustainable marketing strategy so that its products can be widely accepted and demanded by the market. This study aims to: (1) measure the effectiveness of the marketing activities that have been and are currently implemented by the company, (2) identify the key factors that can strengthen the company’s marketing strategy, and (3) formulate the most ideal marketing strategy to increase sales volume, company profitability, and market share. This research is classified as explanatory research and was conducted at PT. Sumber Mulya Grand Organik Blitar, focusing on the company’s marketing management by involving employees as well as consumers of organic fertilizer products. The analytical method used in this study is SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) through the preparation of the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrices, the SWOT matrix, and strategic determination analysis. The results of the SWOT analysis indicate that the most appropriate and optimal strategy with the highest score is the Strength–Threat (ST) strategy, which focuses on utilizing the company’s strengths to overcome external threats. This strategy is implemented through the intensification of distribution channels, optimization of promotional and advertising activities, provision of complete product variants at all company branches, development of an integrated organic farming system, collaboration with farmer groups across Indonesia, provision of free consultation services for farmers, continuous improvement of customer service, clarification of sales targets, facilitation of purchasing and product delivery, and the implementation of a flagship program, namely the “BSP (Pay After Harvest)” program for farmers who meet certain criteria.